Green Synthesis of N-Sulfonylimine in Solvent-Free Condition with Heteropoly Acid as Catalyst - Wang, Desheng; Yan, Liang; Wang, Xiaolai (Asian Journal of Chemistry, 2012)
A new method for the synthesis of N-sulfonylimine directly from benzaldehyde and p-methylphenyl sulphonylamine with Keggin type heteropoly acid as reusable catalyst in solvent-less condition had been investigated. H3PW12 is found to be the most efficient activity and affording N-sulfonylimine in the yield of 86 %. H3PW12 catalyst reserved its' activity and the yield decreased slightly after running for 5 times. The facial catalytic separation and the reusability of the H3PW12 may hopefully contribute to the development of green chemistry and the environmental benign strategy for the synthesis of N-sulfonylimine.